Effects of training, age, gender and selected genes on aerobic endurance performance in cross-country skiing - Johansen, J.-M. (University of South-Eastern Norway, 2021)
The main objective of this thesis was to investigate the effects of training, age, gender and selected genetic variants on aerobic endurance performance and training adaptations in well-trained cross-country skiers. The skiers recruited for the different studies were either exclusively characterized as national-level cross-country skiers (Study I and III) or recreational- to national-level cross-country skiers (Study II). In all studies, both male and female, young and adult skiers were recruited.